Pelatihan Pembuatan Snack Bar dari Tepung Ubi Ungu sebagai Alternatif Camilan Sehat - Martina Widhi Hapsari; Novia Anggraeni; Paulus Damar Bayu Murti; Anggara Mahardika; Windy Rizkiprilisa (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
Snacks are often consumed by people to temporarily relieve hunger. These snacks are usually high in sugar and fat and low in fiber. One of the healthy snacks consumed is a snack bar made from local food. In this training, developing a snack bar based on local food ingredients that is low in calories and high in fiber, namely a snack bar based on purple sweet potatoes flour. The purpose of this training is to introduce the community to product diversification using local food from purple sweet potatoes which can be processed into healthy snacks and basic skills on how to make the snack bar. The methods used in this training are lectures, demonstrations and questions and answers. The stages of implementing the activity are an explanation of local food, using purple sweet potato as a basic ingredient for healthy snacks. Next, the practice of making snack bars with the basic ingredients of purple sweet potato flour, peanuts and crispy rice. The results of the evaluation of the snack bar making training, namely the response of the training participants were very satisfied and enthusiastic in participating in this activity because participants could add new insights and knowledge in terms of local food snack bars. In addition, the training participants also got new business ideas to be developed in healthy snack culinary.